Limonene, a Chemical Compound Related to the Resistance of Eucalyptus Species to Austropuccinia psidii - Silva, Renata R. [UNESP]; Silva, Andre C. da; Rodella, Roberto A. [UNESP]; Marques, Marcia O. M.; Zanuncio, Antonio J.; Soares, Marcus A.; Serrao, Jose E.; Zanuncio, Jose C.; Furtado, Edson L. [UNESP] (Amer Phytopathological Soc, 2020)
The fungus Austropuccinia psidii is a major pathogen of Eucalyptus spp. that damages mainly early-stage leaves. Resistant clones are the most widely used control measure for the rust disease caused by A. psidii. Essential oils produced in the plant-host cells are associated with resistance. However, the chemical characteristics of Eucalyptus leaves at different stages of maturity, associated with resistance or susceptibility to A. psidii, need to be determined. The aims of this study were to characterize the chemical composition of essential oils in Eucalyptus leaves at three developmental stages of clones of three E. urophylla x E. grandis hybrids that exhibit different resistance levels to rust and to identify probable resistance-related compounds from them. The rust severity following inoculation and the quantity and quality of the essential oil extracted by hydrodistillation were determined at the first, third, and fifth leaf stages of the three clones. Identification of the compounds present in the essential oil was determined by gas chromatography coupled with mass spectrometry. No rust was observed on the three leaf stages of the resistant clone or on the fifth leaf stage of the susceptible clones. Limonene was found at high percentages in essential oils from the three leaf stages of the resistant clone and at low percentages in the susceptible clones. In vitro and in vivo tests indicated that low limonene percentages stimulated A. psidii urediniospore germination and were not fungitoxic, whereas high percentages caused complete inhibition of germination and degenerative changes in fungal reproductive structures. The limonene present in Eucalyptus leaves can be considered a chemical compound related to the rust resistance of Eucalyptus spp.
Keywords: Eucalyptus essential oils; eucalyptus rust; gas chromatography; phenology stage; Puccinia psidii; resistance; secondary metabolism